Biotechnology: building on farmers' knowledge - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Biotechnology: building on farmers, knowledge edited by Joske Bunders Bertus Haverkort and Wim Hiemstra 1996 240pp ISBN 0 333 67082 5